Assessment of Women's Knowledge Regarding Family Planning. - Mahmoud Mohamad Al-Suaediany; Salwa H. Al-Moktar (Kufa Journal for Nursing Sciences)
Objective: The aim of the study to determining the women's knowledge regarding contraceptive, and to identify the relationship between women's knowledge and Socio-demographic characteristics (Age, educational level, residence and employment).